Propensity score analysis of outcomes following laparoscopic or open liver resection for hepatocellular carcinoma. Issue 7 (31st March 2016) - Sposito, C; Battiston, C; Facciorusso, A; Mazzola, M; Muscarà, C; Scotti, M; Romito, R; Mariani, L; Mazzaferro, V
Abstract: Background: Liver resection is a potentially curative approach for hepatocellular carcinoma (HCC). Laparoscopic liver resections may reduce complication rates, especially in patients with cirrhosis. The aim of this study was to compare the results of laparoscopic liver resection with those of open liver resection for HCC. Methods: Patients with cirrhosis who underwent minor liver resections for HCC from 2006 to 2013 were identified retrospectively from a prospective database according to the technique adopted (laparoscopic or open). Short- and long-term outcomes were compared between the two groups before and after 1 : 1 propensity score matching. Results: A total of 269 patients were considered: 226 who underwent open liver resection and 43 who had a laparoscopic procedure. The two groups differed at baseline in terms of median age, sex, performance status, tumour location and type of resection. After propensity score matching, two comparable groups of 43 patients each were obtained. Intraoperative bleeding, margin clearance and operative mortality were similar in the two groups, whereas complication rates were lower (49 versus 19 per cent in open versus laparoscopic groups respectively; P = 0·004) and median hospital stay was shorter (8 versus 5 days; P < 0·001) in the laparoscopic group. On multivariable logistic regression analysis, the only independent factor that reduced the risk of postoperative complications was the use of laparoscopy (odds ratio 0·12, 95 per cent c.i. 0·03 to 0·55; P = 0·006). Median overall survival was 57·8 months in the open group and 48·8 months in the laparoscopic group ( P = 0·802). Median disease-free survival was 31·7 and 25·5 months respectively ( P = 0·990). Conclusion: In comparison with the open approach, laparoscopic minor liver resections for HCC improved short-term outcomes, with similar survival results. Abstract : Laparoscopic is better